(untitled) (Journal of Hama University, 2019)
The aim of the research is to know the HR strategy of the Syrian Arab Airlines. The employees’ attitudes towards HR strategy are defined in the Syrian Arab Airlines. To determine the nature of the correlation between the strategy of human resources development in the Syrian Arab Airlines and the trends of the members of the research sample, and according to the research variables. The sample of the research was withdrawn by 10% of the original society by 375 employees. The representation ranged from (11.5%) for the pilots to 39% for the hosts and all the heads of the departments (16) The researcher is a researcher’s trend gauge. The most important results were: 1-There are statistically significant differences between the average responses on the workers’ attitudes scale according to gender variable for females. 2-There are statistically significant differences between the average responses on the workers’ attitudes scale according to the social situation variable for the benefit of the Gazans. 3-There are no statistically significant differences between the average scores of the sample of the research sample on the workers’ attitudes scale according to the change in the professional age. 4-There are statistically significant differences between the average scores of the research sample members on the employee trends scale according to the occupational characterization variable. Were for the benefit of individuals acting as pilots